2009
DOI: 10.1016/j.ejc.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Mixing 3-colourings in bipartite graphs

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 7 publications
5
94
0
Order By: Relevance
“…If k = 3, then k-Colour-Path is in P; while k-Colour-Mixing is coNP-complete (Cereceda et al [13,14]). …”
Section: (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…If k = 3, then k-Colour-Path is in P; while k-Colour-Mixing is coNP-complete (Cereceda et al [13,14]). …”
Section: (B)mentioning
confidence: 99%
“…The proof in [13] of the coNP-completeness of 3-Colour-Mixing uses the concept of folding: given two non-adjacent vertices u and v that have a common neighbour, a fold on u and v is the identification of u and v (together with removal of any double edges produced). The results in Theorem 3.4(b) are clearly the odd ones among the list of results above.…”
Section: (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…This left open the question of connectivity of bipartite graphs (χ(G) = 2) for k = 3; the yes-instances were characterized, and it was shown that the problem of deciding connectedness for bipartite graphs is coNP-complete, but restricted to planar bipartite graphs can be solved in polynomial time [78]. For k = 3, it was shown that the diameter is in O(|V(G)| 2 ) for each connected component (and that this bound is tight, as there exist configurations at distance Ω(|V(G)| 2 )), and that both reachability and shortest transformation can be solved in polynomial time [32].…”
Section: K-coloring Reconfigurationmentioning
confidence: 99%
“…So far, there are no known families where the reconfiguration graph is connected and of superpolynomial diameter; in fact, Cereceda [77,78] conjectured that for k ≥ col(G) + 2, the diameter of the reconfiguration graph is in O(|V(G)| 2 ), and showed that the conjecture is true for the values k = 1 and k = ∆(G) [77]. The results on connectivity also showed quadratic bounds on diameter, including a lower bound on diameter for chordal graphs, culminating in the proof of the conjecture for k ≥ tw(G) + 2 [85].…”
Section: K-coloring Reconfigurationmentioning
confidence: 99%